Electrospun Silsequioxane-grafted PVDF hybrid membranes for high-performance rechargeable lithium batteries. (15th June 2021) - Liu, Lingli; Xu, Tongwei; Gui, Xuefeng; Gao, Shuxi; Sun, Longfeng; Lin, Qiong; Song, Xuan; Wang, Zhongxin; Xu, Kai
Abstract: Microporous electrospun membranes have certain advantages of higher porosities and electrolyte wettability owing to their high specific surface areas, but these materials suffer from insufficient mechanical strength and dimensional stability when they are employed in advanced lithium batteries. In order to improve the material characteristics and electrochemical performance of these materials, we report the fabrication of silsesquioxane modified electrospun hybrid poly(vinylidene fluoride- co -hexafluoropropylene) (PVDF(HFP)) membranes via the combination of concurrent electrospinning/electrospraying techniques and a UV-initiated grafting polymerization method. The fabricated electrospun hybrid membranes were systematically characterized via various techniques, including thermal characterization, morphology observation, dimensional and mechanical property tests, as well as electrochemical measurements. Silsesquioxanes were covalently integrated onto the surface of electrospun fibers to obtain rigid sheath-like hybrid shell architectures and enhanced cross-linked networks, thus imparting these electrospun hybrid membranes with superior mechanical properties, thermal and dimensional stabilities, as well as remarkable electrochemical performance. Through an in-depth investigation into the electrochemical performance differential of separator prepared by different molecular-topological silsesquioxanes, we discovered that octa-silsesquioxanes (SQ-T8 ) decorated separators offered superior cycling performance while deca-silsesquioxanes (SQ-T10 ) exhibited a higher capacity. Through these investigations, we hypothesized that SQ-T8 and SQ-T10 assembled into different configurations via intermolecular stacking arrangements as they were grafted onto electrospun fibers. On the basis of these promising results, these electrospun hybrid membranes could find practical applications in advanced lithium batteries. Highlights: We fabricated a novel silsesquioxane-grafted hybrid electrospun membranes that featured silsesquioxane-based sheath-like protective shells covalently bonded onto electrospun fibers. Theses silsesquioxane-grafted hybrid membranes were successfully prepared via UV-initiated grafting cross-linking reaction that is combined with simultaneous electrospinning/electrospraying methods. Remarkably enhanced mechanical strength and dimensional stabilities of the membranes that is benefiting from the coated silsesquioxane-based protective shell and the formed cross-liked network. Highly improved electrochemical performance, including higher conductivity, lower electrochemical impedance, superior electrochemical stability as well as improved charge-discharge properties.